Migration status and attitude towards authoritarian rule: the case of Singapore's naturalized citizens. (4th May 2018) - Ng, Hoi-Yu
ABSTRACT: Immigration has become a controversial issue in Singapore, an enduring Southeast Asian electoral autocracy. One of the controversies concerns how immigrants would influence Singapore's domestic politics. Drawing on two surveys, this study examines immigrants' views on authoritarian rule, both their attitudes towards Singapore's incumbent regime and their perceptions of democracy and authoritarianism. The results present a mixed picture. On the one hand, immigrants who were naturalized tend to favour the incumbent more than the native-born. They tend to have better evaluations of state institutions and government performance than the native-born. Partial evidence also exists that naturalized citizens are more likely to vote for the incumbent than the native-born. On the other hand, the author found no strong evidence that naturalized citizens are less supportive of democracy or more pro-authoritarian than the native-born. Political and theoretical implications of the findings are discussed.